(untitled) (Research, Society and Development, 2022)
The β-1,3-glucanases synthesized by filamentous fungi have wide applicability in the food, chemical, and pharmaceutical industries. However, its obtainment can be costly, especially due to substrates used to induce its synthesis. Therefore, the objective of this work was to produce β-1,3-glucanase by T. harzianum Rifai using free and immobilized cells in synthetic and plant sponges, using different inducing substrates that could provide better cost-effectiveness for the industrial production of the enzyme. The Petri dish zymogram technique proved to be efficient for screening substrates inducing β -1,3-glucanases against species of filamentous fungi. It was possible to perform the immobilization of T. harzianum in a synthetic sponge allowing the realization of repetitive batches for enzymatic production. All tested substrates resulted in the synthesis of β-1,3-glucanase, including succinoglycan, proposed innovatively in this study. Fungal biomass resulted in the best inducing substrate under conditions of free and immobilized cells, with a production of β-1,3-glucanases of 0.73 U and 0.80 U of β -1,3-glucanases. The substrates corn starch and cassava showed promise in the production of β-1,3-glucanase and maintained production until the fourth batch was evaluated, with values of 0.51 U and 0.46 U of β-1.3-glucanases, respectively. The results obtained in this study showed that the zymogram is a practical method for screening substrates induced by the fungus T. harzianum. Corn starch and cassava are accessible and low-cost sources for β-1,3-glucanase synthesis in repetitive batches, including the use of immobilized and free cells.